THE PREVALENCE OF INCREASING TOTAL CHOLESTEROL AND BODY MASS INDEX IN ELDERLY PEOPLE AT PANTI JOMPO WERDHA TRENA IN GIANYAR BALI (PRELIMINARY STUDIES) - Harinder Kaur; Linawati Ni Made (Bali Journal of Medical and Health Sciences, 2017)
Cholesterol is a type of fat that is found in our blood, which is produced by liver. Hereby this research will be done on elderly in an old folk home called as Panti Jompo Werdha Tresna. The samples that was taken was both female and male, age varies around 60 years old to 80 years old. Blood was taken together with height and weight to make the correlation between all this two variables.The study design for this research is descriptive study. 20 blood samples have been taken. From the data that obtained in the results it is concluded that if the elderly with high body mass index (BMI) tend to have high total cholesterol. Mean serum cholesterol in the study population was 195.25±32.48   mg/dL(>199 mg/dL) in 60% of the investigated men and 53.3% of the investigated women. As a conclusion, in this study found that the prevalence of excess body weight and age is not associated with the prevalence off increasing total cholesterol compare to other studies. Maybe it is because of total population that is taken in this study is very less compare to others. So the results do not really show the prevalence in population. It is advisable to do some research on the elderly with a higher number of samples so that it can represent the condition within population. Keywords: Cholesterol, Body Mass Index, Age